Another Way of Understanding Territory - Sáez, Oscar Calavia (Revista de Antropologia, 2015)
The Yaminawa of Acre (Southwestern Amazon, Brazil) have been considered by government officials and NGOs as a political problem, due to their difficult insertion in the multiculturalist territorial system. Notwithstanding their success in having their lands legally recognized, their groups, constantly split by inner conflicts, remain wandering between ethnic lands and cities. In this paper, we examine Yaminawa political discourse and myths, searching for the conceit of territory that underlie this practice. It can be defined as a sociological and topological rather than ecological conceit. Distance is the main attribute of territory: shifting social arrangements must be modulated by adequate distances. The idea of ethnic territory as an ecological space, useful to reproduce traditional ways of life, is frequently expressed by Yaminawa leaders. However, it is designed, mainly, to fit into the western (and brazilian) preconceptions about the embeddedment of indigenous peoples in the natural world.